(Re) thinking Emotions in Visual Education Activities: Students' Experiences. (25th December 2017) - Casian, Silvia; Lopes, Amélia; Pereira, Fátima
Abstract: This article focuses on the emotions of 13 and 14 year‐old students related to visual art education activities. Our aim is to understand the interference of the students' emotions with the processes of the creation and reception of their own pictures, as well as their characteristics in an art education context. The article adopts a Vygotskian theoretical perspective about emotion and aesthetic education that refers to the biopsychological nature of emotion and its cultural determination. The need to transform emotions in art activities is stressed and the teenagers' pictures are interpreted as a means of communication. The data collection was based on questionnaires and interviews with seventh and eighth grade secondary school students. It is concluded that students' emotions are not only present in the creative process and in its result, but also that they could have a significant positive or negative impact on students' motivation and achievement behaviour in art education classes. In this context, the students' pictures, acting as stimuli, may evoke their emotions.